1980
DOI: 10.1002/1097-0142(19800915)46:6<1307::aid-cncr2820460602>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of susceptibility to cancer. The presidential address

Abstract: The most prominent factor determining susceptibility to cancer is age. However, there is little evidence that the aging process per se increases susceptibility to cancer. Rather, age provides the time necessary for the accumulation of cellular events required for the development of neoplasia. The variations in the patterns of cancer incidence rates seen with age can be explained by alterations in conditions of exposure to carcinogenic stimuli. There is no evidence that the pool of susceptible individuals in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 42 publications
0
39
0
1
Order By: Relevance
“…It is estimated that the incidence of cancer in humans increases between 10 3 ± 10 7 times with advancing age (Miller, 1980). Such clinical observations prompted the multi-hit hypothesis of oncogenesis, which states that cellular transformation is due to an accumulation of somatic mutations.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that the incidence of cancer in humans increases between 10 3 ± 10 7 times with advancing age (Miller, 1980). Such clinical observations prompted the multi-hit hypothesis of oncogenesis, which states that cellular transformation is due to an accumulation of somatic mutations.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the breast, colorectal, and prostate require five to seven driver mutations for cancer initiation and progression, whereas hematological malignancies may require fewer. 6 Some of the well-characterized genes carrying mutations include TP53, RB1, EGFR, and KRAS, which are frequently mutated in various cancer types, whereas others are rare and/or restricted to one cancer. 2 Apart from genomic events that are evident during cancer progression, modifications of the nucleotides, particularly that of the cytosine and post-translational histone modifications, are common in cancer ( Figure 1).…”
Section: Gene Mutationsmentioning
confidence: 99%
“…Extensive genetic studies and statistical models estimate that the number of 'driver' mutations -alterations that causatively contribute to cancer development -depends on the tumor stage. The number of these events varies from five to seven mutations in at least six genes required to convert a normal cell into a cancer cell [29,30] and approximately 80-100 genetic alterations in advanced breast, colorectal and other common solid cancer types [31,32]. Somewhere between these cutoff values, for example 20-40 mutations, may be the number of mutations in pT1a,bN0M0 tumors.…”
Section: Single Mutated Genes and Genetic Networkmentioning
confidence: 99%